Implementasi Sistem Informasi Berbasis Teknologi Dalam Pengelolaan Keuangan Untuk Meningkatkan Transparansi Pada Koperasi Simpan Pinjam Credit Union Bahtera Sejahtera - Melci, Maria; Dilliana , Siktania Maria; Kolit , Yuliana Anggreani Dua Delang (Jurnal Projemen UNIPA, 2026)
Technology-based information systems play an important role in financial management to enhance transparency. Financial transparency is a crucial factor for the sustainability of financial institutions and for building members’ trust. This study aims to analyze the implementation of a technology-based information system in financial management to improve transparency at the Credit Union Savings and Loan Cooperative Bahtera Sejahtera. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that financial management at Credit Union Bahtera Sejahtera has been conducted online using the ESCETE application. Through this application, members are able to independently access financial data, while the financial reporting process is carried out transparently and can be accounted for. Furthermore, financial management is implemented through several stages, including planning and budgeting, recording and processing financial transactions, internal control, reporting and accountability, as well as the application of financial governance and compliance. The implementation of a technology-based information system has proven to enhance transparency, strengthen accountability, and support increased member trust in cooperative management.